2016
DOI: 10.1016/j.str.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Structure of a Novel Globular Domain in RBM10 Containing OCRE, the Octamer Repeat Sequence Motif

Abstract: SUMMARY The OCtamer REpeat (OCRE) has been annotated as a 42-residue sequence motif with 12 tyrosine residues in the spliceosome trans-regulatory elements RBM5 and RBM10 (RBM: ribonucleic acid binding motif), which are known to regulate alternative splicing of Fas and Bcl-x pre-mRNA transcripts. NMR structure determination showed that the RBM10 OCRE sequence motif is part of a 55-residue globular domain containing 16 aromatic amino acids, which consists of an anti-parallel arrangement of six β-strands, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…These results are in line with recent studies which revealed the presence of the an additional globular OCRE domain in RBM10 . The OCRE domain is unique to the splicing factors RBM5 and RBM10, and possibly RBM6 . As with AcD, the sequence‐based domain boundaries annotations of OCRE were unclear and did not represent a self‐folding polypeptide, but more precise structure‐based analysis resulted in the determination of a globular domain with a novel architecture .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in line with recent studies which revealed the presence of the an additional globular OCRE domain in RBM10 . The OCRE domain is unique to the splicing factors RBM5 and RBM10, and possibly RBM6 . As with AcD, the sequence‐based domain boundaries annotations of OCRE were unclear and did not represent a self‐folding polypeptide, but more precise structure‐based analysis resulted in the determination of a globular domain with a novel architecture .…”
Section: Discussionsupporting
confidence: 88%
“…25 The OCRE domain is unique to the splicing factors RBM5 and RBM10, and possibly RBM6. 26 As with AcD, the sequence-based domain boundaries annotations of OCRE were unclear and did not represent a self-folding polypeptide, but more precise structure-based analysis resulted in the determination of a globular domain with a novel architecture. 25 The work with the AcD and OCRE domains illustrates the importance of experimental structure determination and precise structure-based assignment of domain boundaries for less common domains that can confer unique functionalities to subsets of splicing factors, and it shows that NMR is a powerful method for the important task of searching for novel globular domains in multidomain proteins as SYNCRIP and other splicing factors.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the recently reported structure of the RBM10 OCRE domain is highly similar to RBM5 OCRE (backbone coordinate r.m.s.d. 1.1Å) (Martin et al, 2016). Interestingly, mutation of a conserved tyrosine residue (corresponding to Tyr470 in RBM5, where it contributes to the recognition of the PRMs by the OCRE domain) is frequently found associated with lung carcinoma (Imielinski et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In view of its important function it was of keen interest to characterize the molecular conformation of the protein domain that contains the OCRE sequence motif. In earlier work, the three‐dimensional structure of a self‐folding domain containing the OCRE segment has been determined for both splicing factors by NMR spectroscopy in solution, [12,13] and an initial characterization of intramolecular rate processes manifested by ring flipping motions of the tyrosines was described [12] . Here, we now present a quantitative determination of the frequencies of internal motions in these tyrosine‐rich domains, based on integrative use of 1 H NMR experiments and molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%